Nyeburin Marriage Ceremony in Accordance with Balinese Customary Law in Mas Traditional Village - Istri Agung, I Gusti Agung; Kantriani, Ni Ketut; Ramiati, Ni Made (Jayapangus Press, 2024)
The position of sons is critical in customary law societies in Bali. This is related to the belief in the community that if there is no son, there will be no one to carry out customary and religious obligations in a Hindu family. Facing this situation, Balinese customary law combined with Hindu law offers a solution by elevating the status of girls to purusa status, allowing them to have the same rights and responsibilities as boys. The purpose of this study is to describe the Nyeburin marriage ceremony according to Balinese customary law in Mas traditional village. This type of research is qualitative with a phenomenological approach. This research was conducted in Desa Adat Mas. This research uses qualitative data sourced from primary and secondary data. Determination of informants was determined by purposive sampling. The data collection techniques used were observation, interview, literature, and document study. This research used data analysis techniques: data reduction, data presentation, and conclusion drawing. The findings of this study are that Nyeburin marriage has a change in status; namely, the wife has purusa status (male status), so it has consequences for the procedures for implementing marriage, the position of the husband, and the offspring obtained. In Nyeburin marriage, the implementation is also carried out at the purusa residence, which, in this case, is the bride's house. Furthermore, the husband will follow or enter the wife's family environment and legally break away from the bonds of family origin.